An evaluation of Ontario's Group Education Session (GES) for license renewal of seniors aged 80 and above. (February 2016) - Vanlaar, Ward; Hing, Marisela Mainegra; Robertson, Robyn; Mayhew, Dan; Carr, David
Abstract: Introduction: In 1996, the Ministry of Transportation in Ontario (MTO) implemented the Group Education Session (GES), which is a mandatory license renewal program for drivers aged 80 and older. This study describes an evaluation of the GES to assess its impact on road safety in Ontario, as well as its effect on the safety of individual drivers who participated in the program. Methods: Time series analysis of senior driver records both before and after implementation of the GES, and logistic regression and survival analysis examining senior driver records prior to, and following, their participation in the GES. Results: Using time series analysis there is some evidence to suggest that the GES had a positive impact on road safety. According to the other analyses, participation in the GES is associated with a decrease in the odds of collisions and convictions, regardless of whether drivers pass their first attempt of the knowledge test or not. In addition, failing the first road test and/or having demerit points are strong indicators of future collision and conviction involvement. Discussion: Results from this evaluation suggest that the GES has had a protective effect on the safety of senior drivers. Practical Applications: The findings and discussion will help MTO improve the GES program and provide insights to other jurisdictions that have, or are considering, introducing new senior driver programs. Highlights: A licence renewal program for drivers aged 80 and older in Ontario was evaluated. Drivers exposed to the program were compared to comparison groups not exposed. Time series analysis, logistic regression, and survival analysis were used. Results suggest the program had a protective effect on safety of senior drivers.